Una aproximación a la producción de sensibilidad desde las prácticas corporales. El caso de la danza SAMKYA en Medellín (2011)
ABSTRACT: We present preliminary results of a research interest in understanding how the practices help to shape the body and induce sensitivity forms of subjectivity in the contemporary subject. Specifically, we explore the dance technique considered Samkya extracotidiana body, selforiented and directed only at women, which occurs aesthetic discourses and policy provisions. It’s about understanding the ways in which the participants of this practice have represented and experienced body its sensitivity, using the body as an intermediary between the self and society.